Should Offending Religious Feelings Be a Prohibited Act? The Philosophical Analysis of the Article 196 of the Penal Code - Jaworski, Krzysztof Paweł (Studia Warmińskie, 2020)
The article is a philosophical analysis of the crime defined in the art. 196 of the Penal Code as an offending religious feelings. The aim of this work is to reach the axiological sources of the protection of religious feelings in the positive law. In the first part the genesis of this crime in Polish penal codes and other selected legal acts of the 20th century is presented. Then the current legal status in the field of protection of religious feelings is reported. An attempt to define the nature of religious feelings is made. According to the adopted definition, religious feelings are some kind of mental states expressing a person’s attitude towards specific phenomena of his religious world. The author supports the view that religious feelings do not qualitatively differ from all other feelings, and are “religious” only because of their specific subject. Such a concept was adopted by, among others, William James. There are two arguments in this paper to support the thesis that one needs to protect religious feelings: the promotion of personal dignity because of religion or lack of religious beliefs (personalistic argument) and ensuring religious peace (social argument).